Mechanism of traditional Chinese medicine in elderly diabetes mellitus and a systematic review of its clinical application - Zhang, Qiqi; Hu, Shiwan; Jin, Zishan; Wang, Sicheng; Zhang, Boxun; Zhao, Linhua (Frontiers in Pharmacology, 2024)
Objective: Affected by aging, the elderly diabetes patients have many pathological characteristics different from the young people, including more complications, vascular aging, cognitive impairment, osteoporosis, and sarcopenia. This article will explore their pathogenesis and the mechanism of Traditional Chinese medicine (TCM) intervention, and use the method of systematic review to evaluate the clinical application of TCM in elderly diabetes. Method: Searching for randomized controlled trials (RCTs) published from January 2000 to November 2023 in the following databases: Web of Science, Pubmed, Embase, Cochrane Library, Sinomed, China National Knowledge Internet, Wanfang and VIP. They were evaluated by three subgroups of Traditional Chinese Prescription, Traditional Chinese patent medicines and Traditional Chinese medicine extracts for their common prescriptions, drugs, adverse reactions and the quality of them. Results and Conclusion: TCM has the advantages of multitarget and synergistic treatment in the treatment of elderly diabetes. However, current clinical researches have shortcomings including the inclusion of age criteria and diagnosis of subjects are unclear, imprecise research design, non-standard intervention measures, and its safety needs further exploration. In the future, the diagnosis of elderly people with diabetes needs to be further clarified. Traditional Chinese patent medicines included in the pharmacopoeia can be used to conduct more rigorous RCTs, and then gradually standardize the traditional Chinese medicine prescriptions and traditional Chinese medicine extracts, providing higher level evidence for the treatment of elderly diabetes with traditional Chinese medicine.